PENGARUH UMUR PEMOTONGAN DAN LEVEL PUPUK ORGANIK TERHADAP PERTUMBUHAN VEGETATIF RUMPUT BRACHIARIA HUMIDICOLA (Studi Kasus Di Laboratorium Agrostologi Fakultas Peternakan Universitas Sam Ratulangi Manado) - Kurniawan, Dodit .; Anis, Selvie D; ., Rustandi .; Kaunang, W B (ZOOTEC, 2017)
THE EFFECT OF CUTTING AGES AND LEVEL OF ORGANIC FERTILIZER ON VEGETATIVE GROWTH OF BRACHIARIA HUMIDICOLA (Case Study At Agrostology Laboratory Faculty Of Animal ScienceSam Ratulangi UniversityManado)Brachiaria humidicola is a forages as animal feed. Defolation is a proces which is apart of vegetative removed by human or by grazing animals. Brahum is one of perenial species has stolon and has a good  ground cover. From agrostology point of view Brahum needs a good agronomic management and it is not as weeds species.     The aim of this experiment to asses the effect of defolition and level of organic fertilizer on vegetative growth of Brahum Treatments consist of ages of cutting of 30 day and 40 day after triming, and level of organic fertilizer of P1=0 gr; P2=400 gr; P3=800 gr; P4=1200 gr/polybag. Variable measured was the number of stolon, long of stolon and number of tiller. Treatment was arranged factorial 2x4 based on completly randomized design (RAL) with 4 replication.     The results of this research show that the interaction of treatments significandtly effected on all variabel measured, and the best result found at interaction between cutting ages 40 day and level of organic fertilizer 400 gr/polybag. Based on this result it could be concluded that do get the best performance of Brahum need to cut at 40 days regrowth and dosis of organic fertilizer by 400 gr/polybag. Keywords : Age of cutting, organic fertilizer, Vegetative growth, Brahum